Digital currency and banking-sector stability - Chen, William; Phelan, Gregory (Journal of Financial Stability, 2025)
We introduce digital currency into a macro model with a banking sector in which financial frictions generate endogenous systemic risk and instability. In the model, digital currency is fully integrated into the financial system . Stablecoin issuance significantly increases the probability of a banking-sector crisis because it depresses bank deposit spreads, particularly during crises, which limits banks’ ability to recapitalize following losses. While banking-sector stability suffers, household welfare can still improve significantly. Financial frictions nevertheless limit the potential benefits of digital currencies. The optimal level of digital currency could be below what would be issued in a competitive environment. In contrast to stablecoins, which are backed by debt, tokenized deposits backed by traditional bank assets improve welfare without harming financial stability . The scope for welfare gains from stablecoins or tokenized deposits depends on how households value the liquidity services of digital currency relative to traditional deposits and on the cost of issuing stablecoins.